Use of bovine bone graft and bone membrane in defects surgically created in the cranial vault of rabbits. Histologic comparative analysis - Queiroz, Thallita Pereira [UNESP]; Hochuli-Vieira, Eduardo [UNESP]; Gabrielli, Marisa Aparecida Cabrini [UNESP]; Cancian, Daniela Cristina Joanitti (My University, 2006)
Purpose: This study was proposed to analyze histologically the process of repairing bone defects created surgically in the cranial vaults of rabbits. Materials and Methods: Thirty adult male rabbits (Oryctolagus cunilicus) received, under general anesthesia, bilateral parietal osteotomies by means of a 6mm-diameter trephine. The bony defects were divided into 4 groups. In group 1 the defect did not receive any treatment; in group 2 the defect was filled with lyophilized bovine bone (Biograft); in group 3 it was filled with bovine bone and covered with a bone matrix membrane (Bioplate); in group 4 it was covered with a bone matrix membrane. Animals were sacrificed in 3 equal groups at 15, 30, and 60 days. The specimens were subjected to routine laboratory procedures to evaluate the degree of bone repair. Results: After 60 days, new bone formation in group 2 was not satisfactory when compared to that of group 3. Large amounts of new bone formation in maturation were seen in group 3. In the defects covered with a membrane the results were similar to those of group 1 (ie, the cavity was filled with fibrous connective tissue). The implanted bone and membranes were totally resorbed. Discussion and Conclusions: The use of a membrane served as a barrier against the migration of cells from the adjacent tissue and the bone graft/membrane preserved the cavity space, resulting in an enhanced osteogenic effect.
Keywords: Bone grafting; Bone regeneration; Cranial vault reconstruction; Resorbable membranes; Xenografts